2017
DOI: 10.1038/srep40618
|View full text |Cite
|
Sign up to set email alerts
|

Identification of misexpressed genetic elements in hybrids between Drosophila-related species

Abstract: Crosses between close species can lead to genomic disorders, often considered to be the cause of hybrid incompatibility, one of the initial steps in the speciation process. How these incompatibilities are established and what are their causes remain unclear. To understand the initiation of hybrid incompatibility, we performed reciprocal crosses between two species of Drosophila (D. mojavensis and D. arizonae) that diverged less than 1 Mya. We performed a genome-wide transcriptomic analysis on ovaries from pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
22
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 67 publications
15
22
2
Order By: Relevance
“…For Drosophila hybrids, different amplitudes of transcriptome misexpression have been previously reported, which depended on the level of genetic divergence of the parental species. For instance, a recent transcriptomic study of Drosophila mojavensis and Drosophila arizonae (diverged 0.6-1 mya) and their hybrid showed that 12% of genes in the hybrid are DE as compared to the parents (Lopez-Maestre et al, 2017). This is much larger than the fraction of DE genes in this study despite the much lower genetic distance in the Drosophila species.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…For Drosophila hybrids, different amplitudes of transcriptome misexpression have been previously reported, which depended on the level of genetic divergence of the parental species. For instance, a recent transcriptomic study of Drosophila mojavensis and Drosophila arizonae (diverged 0.6-1 mya) and their hybrid showed that 12% of genes in the hybrid are DE as compared to the parents (Lopez-Maestre et al, 2017). This is much larger than the fraction of DE genes in this study despite the much lower genetic distance in the Drosophila species.…”
Section: Discussioncontrasting
confidence: 63%
“…Recent research has studied the effects of this "shock" on different layers of cellular organization, including, among others, the genome (Dutta et al, 2017;Smukowski Heil et al, 2017), the transcriptome (Cox et al, 2014;Hu et al, 2016;Lopez-Maestre et al, 2017), the epigenome (Groszmann et al, 2011;Greaves et al, 2015), and the proteome (Guo et al, 2013;Hu et al, 2017). Specifically, the assessment of transcriptomic changes in hybrids has been used for exploring cis-and transregulation of gene expression (Tirosh et al, 2009;Graze et al, 2012;Li and Fay, 2017;Metzger et al, 2017;Waters et al, 2017).…”
Section: Integrative Omics Analysis Reveals a Limited Transcriptionalmentioning
confidence: 99%
“…A last example that we can cite is the use of Drosophila species as models for speciation studies. This has been done extensively using the species close to D. melanogaster (D. simulans, D. sechellia and D. mauritiana) [38][39][40] and species from the repleta group (D. mojavensis and D. arizonae [41][42][43][44]; D. buzzatii and D. koepferae [45][46][47].…”
Section: A Few Words About Drosophilamentioning
confidence: 99%
“…The degrees of hybrid incompatibility, that is, hybrid sterility and inviability, have been well documented (Ruiz et al 1990). Lopez-Maestre et al (2017) were able to identify the misexpression patterns in hybrids between D. arizonae and D. mojavensis. These 2 species diverged from each other some 1.5 million years ago (mya).…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect in which D. navojoa lags behind its sister species is in gene expression data, which currently is available only for D. mojavensis and D. arizonae , and their hybrids (Wagstaff and Begun 2005; Matzkin 2012; Lopez-Maestre et al 2017; Nazario-Yepiz et al 2017). We remedied this situation, by performing RNAseq in multiple life stages (adults, pupae, and larvae), which resulted in an improved gene annotation.…”
mentioning
confidence: 99%